How packaging colours and claims influence children's vegetable attitude and intake – An exploratory cross-cultural comparison between Indonesia and Denmark. (January 2020) - Angka, Stephanie; Hémar-Nicolas, Valerie; Hapsari, Hanum Putri; Olsen, Annemarie
Highlights: Colours and claims on vegetable packaging, and plate colours were investigated. 132 Indonesian and 84 Danish children aged 8–11 years participated. Willingness to eat, ask parents to buy, recommend to friends, liking and attitude. Plate colour did not influence vegetable intake, but Danish children ate most. No effects of packaging colour and claims, but some cultural differences. Abstract: Most marketing strategies for children focus on unhealthy foods, and it is less well investigated whether they can also be used to promote healthy foods. Furthermore, although it is relevant to know whether marketing strategies perform comparably across cultures, few studies include children from different countries. Therefore, the primary aim of this explorative study was to explore to what extent packaging colours and claims influence children's attitudes to vegetable products, and whether plate colour influences vegetable intake. The secondary aim was to investigate cultural differences between Indonesia and Denmark. A total of 132 Indonesian and 84 Danish children participated. The study consisted of an actual consumption part where cucumbers were served on red, blue, and white plates, and a questionnaire part, where children evaluated cucumber packaging in the three colours with no claim, a healthy claim or a tasty claim. Children rated: willingness to eat (WTE), willingness to ask parents to buy (WTB), willingness to recommend to friends (WTR), attitude towards product, packaging liking, attitude towards packaging, and favourite packaging. Results showed no direct effects of packaging colours and claims on the WTE, WTB, and WTR, and only little influence on product attitude. However, favourite colour influenced packaging colour preference. Plate colour did not influence consumption, but familiarity and liking of the vegetable did. Generally, Indonesian children gave higher product scores than Danish children but consumed less.